Analysis and Improvement of a Construction Permit Approval Process: A Teaching Case for Developing Business Process Development Capabilities, Targeting Developing Nations - Weerasinghe, Kasuni; Bandara, Wasana; Dharmasena, Thanuja; Kuruppubandara, Mahesha; Nawinna, Dasuni (ACIS, 2014)
With the increasing competitiveness in global markets, many developing nations are striving to constantly improve their services in search for the next competitive edge. As a result, the demand and need for Business Process Management (BPM) in these regions is seeing a rapid rise. Yet there exists a lack of professional expertise and knowledge to cater to that need. Therefore, the development of well-structured BPM training/ education programs has become an urgent requirement for these industries. Furthermore, the lack of textbooks or other self-educating material, that go beyond the basics of BPM, further ratifies the need for case based teaching and related cases that enable the next generation of professionals in these countries.